Empyema thoracis in a Nigerian neonate: case report and brief literature review - Ezuruike, Ezinwa O.; Chukwudi, Ndubuisi K.; Nwokeforo, Nathan U.; Obioma, Mary-Anna Ekpe (International Journal of Contemporary Pediatrics, 2021)
Empyema thoracis (ET) is a significant cause of paediatric hospital admissions and mortality but an infrequent finding in the neonatal period. Our case was a three week old male who presented with respiratory distress and had empyema thoracis. He was managed successfully with antibiotics and chest tube thoracostomy drainage.